2022
DOI: 10.1109/access.2022.3215132
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Locating Storage-Based Covert Channels in Internet Protocol Version 6

Abstract: Increased usage of the Internet has risen the demand for more IP addresses across the globe resulting in replacement of IPv4 by IPv6 protocol. Hence, security of IPv6 has become a vital area of research. One of the serious threats to Internet security is the presence of Network Covert Channels (NCCs) that provide substantial aid for performing covered communications like exchanging secret data and/or exfiltrating secret information from the organizations. To detect such malicious activities, there is an urgent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Readers who are interested can view some recent studies that use machine learning or deep learning techniques to thwart covert channel attacks in [29]- [34]. As an example, Dua et al [6] proposed a two-layered system to locate and detect storage covert channels that use the IPv6 protocol. deep neural networks (DNN) and the one-vsrest technique with support vector machine (SVM) are used in their suggested system.…”
Section: Detection Using Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers who are interested can view some recent studies that use machine learning or deep learning techniques to thwart covert channel attacks in [29]- [34]. As an example, Dua et al [6] proposed a two-layered system to locate and detect storage covert channels that use the IPv6 protocol. deep neural networks (DNN) and the one-vsrest technique with support vector machine (SVM) are used in their suggested system.…”
Section: Detection Using Machine Learningmentioning
confidence: 99%
“…Where, in 1987, this concept was expanded to include computer networks [5]. Recent research indicated that the existence of network covert channels, which offer significant assistance for undertaking covered communications including transmitting secret data and/or stealing confidential information, is one of the major risks to internet security [6]. Covert channels in networks, are techniques that aim to hide information in normal network traffic to stay undiscovered [7], and have recently attracted more attention [8].…”
Section: Introductionmentioning
confidence: 99%